[PP.05.25] IMPACT OF SHORT-TERM EXERCISE TRAINING AND BETA BLOCKERS ON ARTERIAL BLOOD PRESSURE AND QT DISPERSION IN PATIENTS AFTER CORONARY ARTERY BYPASS GRAFT SURGERY WITH HYPERKINETIC STATE. (September 2017) - Stoickov, V.; Ilic, M. Deljanin; Stoickov, M.; Tasic, I.; Saric, S.; Andonov, S.; Mitic, S.
Abstract : Objective: The aim of this study was to establish the influence of short-term exercise training and beta blockers (BB) on arterial blood pressure (BP), double product (DP) and QT dispersion (QTd) in patients after coronary artery bypass graft surgery (CABG) with hyperkinetic state. Design and method: The study involved 135 patients after CABG with hyperkinetic state, average age 56.7 years. Patients were randomly divided into the physical training group (TG: 109 patients) and control group (non-training group: 26 patients). In all subjects exercise test on treadmill according to Bruce protocol were performed. TG patients increased doses of beta blockers and are involved in rehabilitation treatment for three weeks. TG patients were instructed to follow a training program using the bicycle ergometer (10 min, 2 times a day) and walking. From standard ECG corrected QT dispersion (QTdc) was calculated. Results: After three days, we have found significant reduction of heart rate from 87.1 ± 5.8 to 75.9 ± 5.5 beats/min (p < 0.001), of systolic BP from 148.5 ± 12.7 to 142.2 ± 9.3 mmHg (p < 0.001), of diastolic BP from 90.3 ± 6.9 to 85.9 ± 4.9 mmHg (p < 0.001) and of DP from 13102.3 ± 797.8 to 12287.6 ± 633.6 beat/min x mmHg (p < 0.001) in the TG. After three weeks, we have found significant reduction of QTdc from 54.5 ± 16.5 to 47.8 ± 14.7 ms (p < 0.005) in the TG. Also, in the TG, we have found significant reduction of heart rate from 87.1 ± 5.8 to 69.9 ± 4.9 beats/min (p < 0.001), of systolic BP from 148.5 ± 12.7 to 136.3 ± 6.7 mmHg (p < 0.001), of diastolic BP from 90.3 ± 6.9 to 82.7 ± 3.8 mmHg (p < 0.001) and of DP from 13102.3 ± 797.8 to 10912.2 ± 602.4 beat/min x mmHg (p < 0.001). In contrast, the non-training group showed no significant changes. Conclusions: The study showed that short-term exercise training and BB have favourable effects on arterial BP, DP and QTd in patients after CABG with hyperkinetic state. Beta blockers are enabled to properly implement and improve the program of physical training in study patients.